Azmat al-Insaniyah fi Syi’ri “Fi Intidzar al-mawt” li Samar Yazbik - Ni'ma Rofidah; Baihaqi Mubarok; M. Faisol (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The Arab Spring is a prominent example of the spread of cross-national regime contention. It is widely accepted that succesfull for regime contention triggered protest in Tunisia and Egypt and other countries. And Syria was one of the countries affected by it revolution. This study aims to examine the poem by Samar Yazbik entitled “Fi Intidzar al-Mawt” which describes the humanitarian crisis that occurred in Syria during the post-Arab Spring when the civil war caused the conflict between the opposition and the government to be a bloodshed. Researchers try to study using Abraham's theory of multilevel needs. The method used in this research is descriptive qualitative analysis with reading and note-taking techniques. And the result of this study is to know clearly that the conflict between the opposition and the Assad regime that broke the peace made Syrians lose their rights as whole human beings. So the conclusion of this study is that this poem shows its expertise in describing the tense conditions of Syria due to the post-Arab Spring conflict.